The Effect of Health Promotion in Improving the Attitudes of Health Students in Carrying Out the Health Protocol to Prevent Covid-19 - Sarma Eko Natalia Sinaga (Journal of Ners and Midwifery, 2021)
The Covid-19 health protocol is a rule or provision made for everyone to be obeyed in order to be able to carry out activities safely during the Covid-19 pandemic. The purpose of this research was to determine the effect of health promotion in improving the attitudes of health students in carrying out health protocols to prevent (Covid-19).The type of research was pre-experimental with a one group pre test and test design, and was carried out in October - December 2020 at AKPER Yatna Yuana Lebak. The sample is all students AKPER Yatna Yuana Lebak, totaling 166 people. The research instrument used was a questionnaire distributed via google form, and the analysis of this research was univariate to see the description of the distribution of respondents before and after the intervention, while the bivariate analysis used the Pair T Test. The frequency distribution of the attitude variable had an overall increase before and after the intervention, while the largest increase occurred in the variable avoiding contact with family and people at home before bathing or changing clothes after doing activities outside the house, which was 3.62%. In the statistical test, the p-valu was 0.017 which stated that there was a significant difference between the attitude before and after the intervention. After the health promotion regarding the prevention and control of Covid-19 was given, it was hoped that health students will be able to practice health protocols such as wearing mask, washing hands with soap, carrying out etiquette coughing/sneezing, bathing and changing clothes after activities outside the house, keeping distance from other people, avoiding frequent touching eyes, mouth and nose, checking their health if they feel fever.Â  These all are in order to make them and their family can stay protected from Covid-19 and they can be the example for the surrounding community in implementing health protocols.